Red lists for cultivated species: why we need it and suggestions for the way forward - Padulosi, S.; Bala Ravi, P.; Rojas, W.; Sthapit, S.R.; Subedi, A.; Dulloo, Mohammad Ehsan; Hammer, K.; Vogel, R.; Antofie, M.M.; Negri, V.; Bergamini, N.; Galluzzi, Gea; et al. (Bioversity International, 2012)
The world's food basket is today shrinking at an alarming rate and most concerning is the reduction in the number of species and varieties used by humankind for food and nutrition, which raises serious concerns about the sustainability of feeding the world today and in the future. Yet, whereas we deploy consistent efforts in monitoring the status of wild biodiversity, very limited is the research in monitoring diversity of plants used by farmers, assess threats of genetic erosion, understand how diversity is helping farmers in coping with climate change, etc. Documenting and monitoring agrobiodiversity on farm is fundamental for enhancing its sustainable use and prevent losses of both genetic diversity and indigenous knowledge to happen before it is too late. This poster explains why a Red List for Cultivated Species is needed and a proposed approach to creating one.